2021
DOI: 10.3390/metabo11070450
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Independent Retinal Phenotypes in an Aldose Reductase Transgenic Mouse Model

Abstract: Aldose reductase (AR), the first and rate-limiting enzyme of the polyol pathway, has been implicated in the onset and development of the ocular complications of diabetes, including cataracts and retinopathy. Despite decades of research conducted to address possible mechanisms, questions still persist in understanding if or how AR contributes to imbalances leading to diabetic eye disease. To address these questions, we created a strain of transgenic mice engineered for the overexpression of human AR (AR-Tg). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…We observe that Sorbinil treatment plays a role in delaying distal axonal degeneration one week after ONC. Our results further corroborate a recent study showing that AR overexpression transgenic mice significantly lose their RGCs, which could be rescued by AR inhibition 78 .…”
Section: Discussionsupporting
confidence: 92%
“…We observe that Sorbinil treatment plays a role in delaying distal axonal degeneration one week after ONC. Our results further corroborate a recent study showing that AR overexpression transgenic mice significantly lose their RGCs, which could be rescued by AR inhibition 78 .…”
Section: Discussionsupporting
confidence: 92%
“…The AR polyol pathway induces inflammation by activating ROS production as well as NF-κB and p38/MAPK signaling [ 22 , 24 , 37 , 38 , 39 , 40 ]. In the eyes, AR inhibition alleviates endotoxin-induced microglia activation in the retina [ 17 , 32 , 41 ] and AR overexpression leads to RGC loss [ 18 ]. We next ask whether results taken from RGCs can be extrapolated to the rest of the brain/CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, increased AR in transgenic mice increases microglia migration into the inner and outer nuclear layers of the retina [ 17 ]. Another study showed that activated microglia infiltrated into the retina of transgenic mice overexpressing AR, resulting in retinal ganglion cell (RGC) loss [ 18 ]. Because AR plays a critical role in microglia activation and retinal neurodegeneration, we asked whether AR also regulates β-amyloid-induced microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus. to determine the importance of AR and the polyol pathway in glucose-dependent growth retardation in aldolase B KO mice, we decided to test the efficiency of sorbinil, a well-characterized AR inhibitor [15,16]. To this end, we first exposed aldolase B KO mice to 0% control or 15% glucose solutions for 6 weeks, and then animals were subsequently divided into the same glucose solutions containing either vehicle or sorbinil (0.25 mg/mL) for another 6 weeks (Figure 2H, left).…”
Section: Resultsmentioning
confidence: 99%